Deixis Used by the Character in Curious George: The Royal Monkey Movie - Diana Sofya; Adip Arifin (English Language Education Department, Universitas Majalengka, 2023)
The present study is aimed at identifying the types of deixis used by Ted and Princess Isabel as the character in the Curious George: The Royal Monkey movie. Further, this present study is also aimed at finding out the most dominant deixis as well as the reason for using the deixis. This research employed Levinson’s theory to analyze the deixis used by characters in Curious George: The Royal Monkey movie. The researcher used the qualitative descriptive method. The present study took Ted and Princess Isabel’s utterances as the source of data. Interactive model of analysis, as suggested by Miles and Huberman, is used to analyze the data. The result of this research showed 177 data that contained 415 deixis. The data discovered Levinson’s five types of deixis. There were 285 data belongs to person deixis, 29 data belongs to temporal/time deixis, 45 data belongs to spatial/place deixis, 38 data belongs to social deixis and 18 data belongs to discourse deixis. To sum up, the person deixis become the most dominant one used by the characters. The reason for using deixis was to make it easy in pointing person, time, place, social, and discourse.